The application of the Theory of Planned Behaviour to prevent medication errors: a scoping review: Medication errors and Theory of Planned Behaviour - Dionisi, Sara; Di Simone, Emanuele; Franzoso, Valeria; Caldarola, Elena; Cappadona, Rosaria; Di Muzio, Flavio; Giannetta, Noemi; Di Muzio, Marco (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work: A safer drug therapy is a relevant aspect of nursing care and an essential component of the clinical governance function. Nurses are key players in the identification and prevention of medication errors that could occur in the drug management process. In the literature there is a particular interest to environmental and organizational factors, while, as we know, the subjective components are little considered. In psychology, the theory that prefers individual factor, at the expense of the environmental one, is Theory of Planned Behavior (TPB), although it has been little applied in the health field. The aim is to search the existing literature on the medication errors and the TPB to predict the intentions that foreshadow risk behaviours of nursing interns. Methods: This scoping review is grounded by Arksey and O’Malley’s framework. Results: Attitude is the most determining predictor of intention. For many students reporting an error would lead to a loss of trust in the nursing profession and this could prevent the report. Nevertheless, some of them affirmed to be positively judged when they did it. It was then observed that a better education on safety raised the level of self-confidence and the sense of responsibility of the students, making them more inclined to the drug therapy management.Conclusions: The Theory of planned behaviour is essential to forerun the behavioural intention of students on the pharmacological safety and the collaborative practice through predictive factors, as attitude, subjective norms and perceived behavioural control.